Boron Nitride Membranes with a Distinct Nanoconfinement Effect for Efficient Ethylene/Ethane Separation. (19th August 2019) - Dou, Haozhen; Jiang, Bin; Xu, Mi; Zhang, Zhen; Wen, Guobin; Peng, Feifei; Yu, Aiping; Bai, Zhengyu; Sun, Yongli; Zhang, Luhong; Jiang, Zhongyi; Chen, Zhongwei
Abstract: A BN membrane with a distinct nanoconfinement effect toward efficient ethylene/ethane separation is presented. The horizontal and inclined self‐assembly of 2D BN nanosheets endow the BN membrane with abundant percolating nanochannels, and these nanochannels are further decorated by reactive ionic liquids (RILs) to tailor their sizes as well as to achieve nanoconfinement effect. The noncovalent interactions between RIL and BN nanosheets favor the ordered alignment of the cations and anions of RIL within BN nanochannels, which contributes to a fast and selective ethylene transport. The resultant membranes exhibit an unprecedented separation performance with superhigh C2 H4 permeance of 138 GPU and C2 H4 /C2 H6 selectivity of 128 as well as remarkably improved long‐term stability for 180 h, outperforming reported state‐of‐the‐art membranes. Abstract : BN‐Nanofilter : Eine BN‐Membran mit ausgeprägtem Nanoconfinement‐Effekt für eine effiziente Ethen/Ethan‐Trennung wird vorgeschlagen und entwickelt. Sie bildet sich aus dem Nanoconfinement reaktiver ionischer Flüssigkeiten in filternden Nanokanälen aus der Selbstassemblierung von BN‐Nanoschichten.